Partially premixed combustion simulation using a novel transported multi-regime flamelet model. (February 2022) - Shan, Fanli; Zhang, Dingrui; Hou, Lingyun; Fang, Hong; Zhang, He
Abstract: To account for partially premixed process in combustion, a novel transported multi-regime flamelet model, which gives local contributions of premixed and non-premixed regimes, is proposed with a theoretical derivation of the governing equation of the premixed weighting coefficient. The model intrinsically ensures mass conservation and physically incorporates transport properties. Thus, it avoids artificial treatment that has to be employed in algebraic multi-regime flamelet models. An ethylene-fueled combustion in a scramjet model combustor is simulated using the transported multi-regime flamelet model. The pressure distribution that characterizes the flame anchoring position and wave distribution is well predicted by the model. It is observed that the premixed regime is distributed mainly in the recirculation zone upstream of the fuel orifice, inside the cavity and close to the lower wall. Besides, there is an apparent instantaneous distribution of the premixed regime in the fuel jet wake, which is attributed to the enhanced premixing by transient vortices. However, the overall contribution of the premixed regime is not as great as that of the non-premixed one, indicating that combustion is non-premixed dominated. The evolution of the OH concentration shows that the OH first emerges close to the cavity ramp. After that, it propagates upstream into the cavity and meanwhile downstream along the lower wall of the expanding section. The isoline of the premixed weighting coefficient used to mark the temperature interface reveals that the premixing can enhance combustion. In contrast, numerical oscillations and a pseudo regime distribution indicating a premixed-dominated combustion that conflicts the physics is observed in a reference simulation using an algebraic multi-regime flamelet model. It is thus demonstrated that the transported multi-regime flamelet model is superior over the algebraic one in the prediction of partially premixed combustion with multi-regimes involved. Highlights: A novel transported multi-regime flamelet model is proposed and derived. The model avoids pseudo regime prediction comparing with algebraic model. The model can reveal regime distribution and its effect on combustion.